2012
DOI: 10.1093/intqhc/mzs058
|View full text |Cite
|
Sign up to set email alerts
|

The association of health workforce capacity and quality of pediatric care in Afghanistan

Abstract: Enhancing workforce capacity and competency and ensuring appropriate supervision and systems support mechanisms can contribute to improved quality of care. Although the results indicate sustained improvements over the study period, further research on the mixture of provider skills, competency and factors influencing provider motivation are essential to determine the optimal workforce capacity in Afghanistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Although this number was small, the observation could stimulate the question of how many other health workers in Afghanistan retain knowledge and practice from previous 11-Day trainings. This finding is in line with that of the IMCI Working Group in 2007 which revealed low IMCI implementation amongst previously trained health workers (almost exclusively doctors) but it differs from larger cross-sectional studies that have demonstrated some benefit of previous IMCI training on quality of care (9,10,17). The 7-Day trainees classified fever as malaria less often than the 11-Day trainees (47% versus 71%), an observation that could have resulted from a difference in malaria incidence in the region during the two month period of the evaluation or due to the fact that the 7-Day course algorithm for fever was stratified into high incidence and low incidence areas.…”
Section: Direct Observation Integrated Management Of Childhood Illnessupporting
confidence: 84%
See 3 more Smart Citations
“…Although this number was small, the observation could stimulate the question of how many other health workers in Afghanistan retain knowledge and practice from previous 11-Day trainings. This finding is in line with that of the IMCI Working Group in 2007 which revealed low IMCI implementation amongst previously trained health workers (almost exclusively doctors) but it differs from larger cross-sectional studies that have demonstrated some benefit of previous IMCI training on quality of care (9,10,17). The 7-Day trainees classified fever as malaria less often than the 11-Day trainees (47% versus 71%), an observation that could have resulted from a difference in malaria incidence in the region during the two month period of the evaluation or due to the fact that the 7-Day course algorithm for fever was stratified into high incidence and low incidence areas.…”
Section: Direct Observation Integrated Management Of Childhood Illnessupporting
confidence: 84%
“…The fact that non-physicians performed less well in the counselling score is surprising in light of the literature and additional research would be necessary to elucidate this further (21). Previous studies in Afghanistan have also identified that female health workers performed better in counselling and providing quality care to children, findings not substantiated by this evaluation (10,19). In this evaluation, two physicians in the 7-Day group and three physicians in the 11-Day group had previously completed an 11-Day IMCI course, yet when these five doctors were excluded from outcome variable calculations, minimal differences in test scores and in summary variable scores were demonstrated.…”
Section: Direct Observation Integrated Management Of Childhood Illnescontrasting
confidence: 56%
See 2 more Smart Citations
“…Afghanistan ranks 175th (out of 185 countries) on human development index (HDI) rankings, with one of the highest child and maternal mortality rates globally (under-5 mortality 64 per 1000 live births; maternal mortality ratio 327 per 100 000 live births) (16). Health workforce capacity is at one-third of WHO recommendations (7.26 doctors/nurses/midwives per 100 000 population) (17,18) and poor quality of care is impairing progress in maternal and child health (19,20). Professional and pharmaceutical regulation is weak, research capacity and access to evidence is severely limited, and large gaps remain in health service management, broader social support systems and infrastructure (17).…”
Section: Clinical Guidelines In Afghanistanmentioning
confidence: 99%